2003
DOI: 10.1097/01.hjr.0000106836.977722.cf
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of electrocardiographic left ventricular hypertrophy to mortality and cardiovascular morbidity in high-risk patients

Abstract: In patients with CV disease simple, easily applicable ECG criteria for LVH identify a subset of individuals at particularly high risk for death and for heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…16,17 In this longitudinal population-based study, the risk of fatal and nonfatal CV morbid events increased from threefold to eightfold higher in middle-aged persons with ECG-LVH compared to normal adults of similar age, and this finding remained significant after adjustment for coexistent risk factors. It should be noted that these findings relate to ST-T abnormalities (LV strain defined as ST-J point depressionX0.1 mV þ inverted 12 In this landmark trial, LVH defined solely by the Sokolow-Lyon voltage criterion was found to be an independent predictor of all cause deaths, CV death and heart failure. 12 The association with risk of heart failure was particularly pronounced (a twofold increase), considering the fact that all patients had normal LV ejection fraction at study entry.…”
Section: Voltage Ecg Lvh Criteria As a Prognostic Indicatormentioning
confidence: 70%
See 1 more Smart Citation
“…16,17 In this longitudinal population-based study, the risk of fatal and nonfatal CV morbid events increased from threefold to eightfold higher in middle-aged persons with ECG-LVH compared to normal adults of similar age, and this finding remained significant after adjustment for coexistent risk factors. It should be noted that these findings relate to ST-T abnormalities (LV strain defined as ST-J point depressionX0.1 mV þ inverted 12 In this landmark trial, LVH defined solely by the Sokolow-Lyon voltage criterion was found to be an independent predictor of all cause deaths, CV death and heart failure. 12 The association with risk of heart failure was particularly pronounced (a twofold increase), considering the fact that all patients had normal LV ejection fraction at study entry.…”
Section: Voltage Ecg Lvh Criteria As a Prognostic Indicatormentioning
confidence: 70%
“…It should be noted that these findings relate to ST-T abnormalities (LV strain defined as ST-J point depressionX0.1 mV þ inverted 12 In this landmark trial, LVH defined solely by the Sokolow-Lyon voltage criterion was found to be an independent predictor of all cause deaths, CV death and heart failure. 12 The association with risk of heart failure was particularly pronounced (a twofold increase), considering the fact that all patients had normal LV ejection fraction at study entry. A link between diastolic dysfunction and ECG LVH was postulated.…”
Section: Voltage Ecg Lvh Criteria As a Prognostic Indicatormentioning
confidence: 70%
“…In contrast, Lonn et al 32 found no difference in the baseline prevalence of diabetes among high-risk patients with and without ECG LVH by Sokolow-Lyon voltage criteria enrolled in the Heart Outcomes Prevention Evaluation (HOPE) trial (39.1% versus 38.1%). The present study demonstrates that diabetes is associated with an increased prevalence and severity of ECG LVH by Cornell product criteria and that this association is independent of clinical , and all-cause mortality (E) by time-varying presence or absence of LVH by Cornell voltage-duration product criteria using a threshold value of 2440 mm · ms. DM indicates patients with diabetes; non-DM, patients without diabetes; and n, number of patients in each group at baseline and at 2 and 4 years of study.…”
Section: Diabetes and Lvhmentioning
confidence: 93%
“…1 Electrocardiography (ECG) has the advantages of low costs, simplicity and almost ubiquitous diffusion; LVH detected by the Sokolow-Lyon index (SV 1 þ RV 5-6 >38 mm) or by the Cornell voltage QRS duration product (>2440 mm*ms) is an independent predictor of CV events, 2,3 and ECG can also be used to detect patterns of ventricular overload or 'strain' (known to indicate more severe risk), 2 ischaemia, conduction defects and arrhythmias. However, it is well known that the sensitivity of ECG to detect LVH is low, independently of the definition of LVH.…”
Section: Introductionmentioning
confidence: 99%